PREVALENCE OF GROUP B STREPTOCOCCUS AND RELATED FACTORS AT THU DUC GENERAL HOSPITAL: A CROSS-SECTIONAL STUDY (Vietnam Journal of Community Medicine, 2026)
Background: Group B Streptococcus infection in pregnant women is a significant cause of early neonatal infections, chorioamnionitis, sepsis, and increased perinatal mortality. Globally, the prevalence of GBS ranges from 10% to 30%, depending on the region, while in Vietnam, studies indicate a trend of increasing prevalence. However, differences between population groups, hospital levels, and prenatal care models have not been fully described. This highlights the need for epidemiological assessment of GBS in local contexts to optimise screening and prevention strategies. Thu Duc General Hospital is a tertiary care facility located in the eastern part of Ho Chi Minh City, serving a large number of pregnant women from both urban and rural areas with diverse sociological characteristics. However, to date, no systematic study has been conducted to determine the prevalence of GBS infection and related factors at this hospital. The lack of local data makes it challenging to develop effective screening strategies, identify high-risk groups, and optimise the effectiveness of prophylactic antibiotic treatment during labour. Objectives: to determine the prevalence of GBS infection and related factors.Materials and methods: A descriptive cross-sectional study. Pregnant women with a gestational age of ≥ 37 0/7 weeks who were admitted and underwent delivery at the Labor and Delivery Unit of Thu Duc General Hospital.Results: The majority of pregnant women were aged between 30 and 39 years (56.5%). The average age of the study sample was 29.66 ± 4.95 years, ranging from 19 to 40 years old. The urban population predominated (56.5%), while the urban population accounted for 43.5%. There were 33 cases of GBS infection among pregnant women (28.7%). The average BMI was 22.1 ± 2.97, with the majority (66.1%) belonging to the normal BMI group of 18.5–22.9, followed by two groups with a BMI ≥23, totalling 27.8%. Pregnant women with vaginitis had a 6.37 times higher rate of GBS infection compared to the group without vaginitis (p=0.000). The rate of GBS infection was higher in pregnant women with a BMI of 23 or greater compared to the BMI group (OR = 1.46), but the difference was not statistically significant. Pregnant women ≥ 35 years old had a higher risk of GBS infection than pregnant women < 35 years old (OR = 1.94); the difference was not statistically significant.Conclusion: Pregnant women who develop vaginitis during pregnancy have a higher rate of group B streptococcal infection compared to those who do not develop vaginitis.
Keywords: Group B streptococcal (GBS) infection, vaginitis, cesarean section, group B streptococcal test, overweight/obesity.